PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY BERBASIS ANDROID PADA MATERI JARINGAN KOMPUTER DAN INTERNET DIKELAS VIII SMP LKIA PONTIANAK - Rahmawati; Sri Koriaty; Dini Oktarika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of digital technology demands innovative learning media that can increase student interest and understanding, particularly in abstract topics such as computer networks and the internet. This study aims to develop an Android-based Augmented Reality (AR) learning medium and to examine the feasibility and response of eighth-grade students at SMP LKIA Pontianak to the developed medium. The theoretical basis of this research includes the concept of learning media, learning theory, augmented reality technology, and the Android operating system relevant to technology-based learning. The research method used is Research and Development (R&D) with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Data collection instruments included observation, interviews, questionnaires, and documentation, with data analysis using a Likert scale. The results indicate that the Android-based AR learning medium is categorized as very feasible based on assessments by media experts, material experts, and small- and large-scale trials. Furthermore, student responses indicated a high level of interest and understanding. Thus, the Android-based AR learning medium is effective as a supporting tool for informatics learning in junior high schools.